A co-design approach for stakeholder engagement and knowledge integration in flood risk management in Vhembe district, South Africa - Mugari, Ephias; Nethengwe, Nthaduleni Samuel; Gumbo, Anesu Dion (Frontiers in Climate, 2025)
IntroductionParticipatory methods and collaboration among diverse knowledge holders are critical to soliciting multiple, and often competing, stakeholder perspectives and knowledge systems for enhancing flood management.MethodsThis study uses a participatory co-design workshop, post-workshop survey, and key informant interviews to establish the utility of co-design methods in engaging diverse stakeholders, including flood-prone communities, in flood management and/or adaptation in South Africa’s Vhembe district. The co-design workshop brought together policymakers, practitioners, political actors, government agencies, local authorities, traditional leaders, and four flood-prone communities. It was conducted in the flood-prone region in the last quarter of 2023. At that time, discussions on mainstreaming climate change adaptation and disaster risk reduction in the development planning process were underway.ResultsThe results show that the stakeholders were able to establish the key drivers of flood risk, challenges associated with flooding, current flood response measures, and barriers to effective flood response. However, an urgent need was for more effective flood response and an active role of flood-prone communities in the district. Stakeholders were able to use insights from the current dissemination of flood early warning systems and networks created during the workshop to call for action toward a community-based flood early warning system in the district. This call to action was premised on genuine collaboration between flood-prone communities and other key stakeholders rather than on any specific interventions. This was key to fostering more open discussions on enhancing the district’s flood response and early warning systems.ConclusionThe study concludes that the co-design approach with diverse knowledge holders is enriched by the local context and insights provided by the flood-prone communities (top-down collaborating with bottom-up) even beyond the workshop. This is useful for developing and implementing future community-based flood early warning systems.